Ancient Rome [videorecording (DVD)] : the glorious empire. (Lost treasures of the ancient world., 2006)
The Roman Empire gave history one of its most eventful and colorful periods. Its legacy remains for all to see in the incredible civic buildings, temples, and theaters of the ancient city.